DAMPAK WISATA PANTAI MINANGA TERHADAP EKONOMI LOKAL MASYARAKAT DESA KOTAJIN UTARA KABUPATEN GORONTALO UTARA - Danial Hasan; Sri Nuryatin Hamzah; Sitti Nursinar (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2022)
Coastal tourism is progressing rapidly along with the development of digital technology, especially the development of social media. Various information on newly opened beach tourism locations was introduced on social media, thereby attracting tourists to visit, and ultimately opening up business opportunities for local communities in tourist areas. This study aims to determine the impact of Minanga Beach tourism on the people's economy of Kotajin Utara Village. The research was carried out for six months, from February 2021 to August 2021, located in the Minanga Beach area, Kotajin Utara Village, Gorontalo Utara Regency. The method used in this study is the interview method. A total of 99 tourist respondents, 32 business unit owners, and 24 workers were interviewed to see the impact of tourism on the community's local economy. Keynesian Income Multiplier and Multiplier analyses were used to determine the direct, indirect, and continued influence of Minanga beach tourism. The results showed that Minanga Beach tourism had an impact on the local economy of the people of Kotajin Utara Village, Atinggola District, Gorontalo Utara Regency, with the Keynesian Income Multiplier value of 1.77, Ratio of Income Multiplier Type I of 1.13, and Ratio of Income Multiplier Type II of 1.70.